Biomonitors of urban air pollution: Magnetic studies and SEM observations of corticolous foliose and microfoliose lichens and their suitability for magnetic monitoring - Chaparro, Marcos Adrián Eduardo (2013)
This study explored the suitability of available lichen species as air pollution biomonitors and assessed their potential for magnetic monitoring in cities. Several lichens on tree bark were collected in urban and industrial sites from Tandil city, as well as control sites. The results showed that magnetite-like minerals were the main magnetic carriers in all sites and samples. However, the concentration varied between clean and polluted sites. In addition, magnetic-grain size-distribution showed clear differences between sites. Observations by scanning electron microscopy showed different particles in a variety of shapes and grain sizes; moreover, the presence of iron oxides and several toxic elements was detected by energy dispersive spectroscopy analysis. Although eleven lichen species were identified that appeared suitable for use as air-pollution monitors, three of them, Parmotrema pilosum, Punctelia hipoleucites and Dirinaria picta, occurred more frequently in the area, thus constituting appropriate species for future monitoring in the study area.